P71 - A. Leshchenko; N. Matsenko (EJC Supplements, 2015)
Breast cancer is the most common cause of death from cancer among women aged 40–69 years. According to WHO, about 1 million new cases of breast cancer are diagnosed annually worldwide, and nearly 500,000 die from it. In Russia, more than 55,000 women are diagnosed with breast cancer annually, and more than 22,000 die from it. Diagnosis and treatment of breast cancer is the primary and important social and medical problem.The increased expression of: (a) ER and PgR (70–75% of all cases of breast cancer) is an indication for hormone therapy, which is one of the simplest and most effective methods of systemic treatment of breast cancer; (b) receptor HER2/neu is a marker of highly aggressive form of breast cancer and indication for the use of targeted therapy Gertseptin; (c) proliferative factor Ki-67 reflects the ability of a tumor to metastasize. Today, the “gold standard” of gene expression diagnostic of ER, PgR, HER2/neu and Ki-67 in breast cancer is immunohistochemistry (IHC) using foreign test systems (Ventana, Dako Inc, USA) . However, IHC diagnostics has some significant drawbacks. It leads up to 15–17% of cases of incorrect choice of drug therapy, which based on incorrect results of IHC studies. As a result, the significant group of patients do not receive effective treatment. Aim of the study Aim: the development a prototype of diagnostic test system for detection the receptor status of breast cancer, based on RT-PCR. Materials and methods: Breast cancersamples consisted of 45 fresh-frozen tissue (FFT) samples of breast cancer (sites of malignant transformation and normal tissue from the same patients) and 59 FFPET sampleswere collected. All the samples had the IHC characteristic of receptor status of ER, PgR, HER2/neu and proliferation factor Ki-67 (Dako Inc., USA). Samples were submitted by SBIH NR “Novosibirsk Regional Oncology Center” (Novosibirsk, Russia). The experimental part of the study was divided into several stages: separation of mRNA from cells, obtaining cDNA (reverse transcription reaction), PCR in real-time and validation of the test system. Isolation of total RNA from FFT samples was performed using a set of “SV Total RNA Isolation system” according to the manufacturer’s instructions (Promega, USA). Isolation of total RNA from FFPET samples was performed using a set “ReliaPrep FFPE Total RNA Miniprep System” (Promega, USA) according to the manufacturer’s instructions. The concentration of total RNA was determined using a NanoDrop 1000 microspectrophotometer (Thermo Bioscience, USA) (RNA concentration were 15–660 ng/ml). Results: For the reverse transcription reaction (RT) and PCR, the main parameters were selected. For RT: RNA incubation time and temperature of the reaction, enzyme concentration in the reaction mix. For PCR: the amount of DNA template, the number of primers, the concentration of magny ions, the concentration of the polymerase. Validation of the developed test system was carried out by comparing the results obtained by RT-PCR with the results of the IHC analysis of the same samples. Statistical processing of the research results was performed using the MedCalc program v.14.12.0 (Microsoft Corp.). Conclusion: We have considered modern advanced methods of diagnostic of breast cancer receptor status. It was concluded that the use of RT-PCR in real time technology is the best alternative technology of the IHC, which currently is the standard definition of the expression of ER, PgR, HER2/neu and Ki-67. Prototype of test system for the detection of ER, PgR, HER2/neu and Ki67 proliferative factor in breast cancer samples was designed and optimized by RT-PCR.